Osteoid osteoma of the distal phalanx of the finger: Case report and review of literature - Ashima Kundu, BS; Liana Ysabel Almendras Bautista, BS; Haley Clark, BS; Usman Beg, DO; Amirmasoud Negarestani, MD; Emad Allam, MD (Radiology Case Reports)
Osteoid osteoma (OO), a benign bone-forming tumor estimated to account for 3% of all primary bone tumors, rarely occurs in the finger. This case report presents an unusual instance of osteoid osteoma in the finger of a 15-year-old male patient. The lesion was discovered following an initial patient visit for left middle finger pain and swelling for one year without any identifiable injuries.